Comment on: "Measurement of deviations of transition probability of the neutral silver lines at 827.35 and 768.77 nm using OES-technique" by Alhijry et al. [JQSRT (2020) 106922]. (November 2020) - Aberkane, Sabrina Messaoud; Palleschi, Vincenzo
Highlight: Identification of the neutral silver line at 768.77 nm. Interference of the silver line at 768.77 nm with another emission line. Measurement of deviations of transition probability of the neutral silver lines at 827.35 and 768.77 nm using OES-technique. Abstract: In this comment we pointed out an error in the identification of the neutral silver line at 768.77 that invalidates some of the results reported in the paper "Measurement of deviations of transition probability of the neutral silver lines at 827.35 and 768.77 nm using OES-technique" by Alhijry et al., recently published on JQSRT.